Law Enforcement Against the Crime of Smuggling Methamphetamine Narcotics by Sea in the Tanjung Balai Area - Wahyu Numan Prasetya; Henry Aspan; Fitri Rafianti (Judge : Jurnal Hukum, 2026)
The smuggling of narcotics particularly methamphetamine through maritime routes in coastal areas of Indonesia particularly in Tanjung Balai has become a highly pressing legal issue due to its detrimental impact on communities and social stability. This study aims to analyze law enforcement against the crime of methamphetamine smuggling by sea in the Tanjung Balai area and identify the obstacles faced by law enforcement officials. This study uses a normative legal approach, collecting legal materials through a literature review, including laws, related regulations, and court rulings. The main findings of this study indicate that despite existing regulations, law enforcement in the field is hampered by limited human resources and technology, as well as weak inter-agency coordination. Other obstacles include the influence of international networks and corrupt practices, which exacerbate the situation. This study recommends the need for an evaluation of the law enforcement system, strengthening inter-agency coordination, and the use of advanced technology to improve oversight. The implications of these findings are the importance of improving policies and increasing the capacity of law enforcement officials, particularly in areas prone to smuggling.